Violence-Related Injuries: The Most Common Cases in Hyderabad, Pakistan: Cases of Violence-Related Injuries - Bibi, Ishrat; Shaikh, Muhammad Rafique; Munir, Ummara; Samad, Abdul; Aslam, Nadia; Rasheed, Aisha (Pakistan Journal of Health Sciences, 2024)
The law influences every aspect of human activity, including medical practice. The nature of casualty is affected by geographical regions, cultures, and social values. Determining characteristics of casualty can guide health policy and can assist in managing healthcare resources. Objective: To profile the cases at casualty department of a tertiary teaching hospital. Methods: The study was conducted at the casualty department of Liaquat University Hospital Hyderabad, Pakistan and Department of Forensic Medicine & Toxicology LUMHS, Jamshoro, over a period of one year from January 2021 to December 2021. A total of 3,487 cases were recorded and categorized into violence-related, transportation-related, substance-related, and sexual assault-related injuries. Results: The majority of cases were violence-related incidents (84.65%), followed by transportation-related accidents (14.65%), substance-related injuries (3.61%), and sexual assault-related injuries (0.69%). Violence-related injuries were divided into assault cases, firearm incidents, and police torture. Transportation-related injuries were categorized as road traffic accidents and train accidents. Assault and road traffic accidents were the leading cause of violence-related and transportation-related injuries, respectively. The highest numbers of cases were observed in April, June, and May. Conclusions: A substantial portion of cases at casualty department of Liaquat University Hospital, Hyderabad is contributed by violence-related injuries